2017
DOI: 10.1097/md.0000000000005805
|View full text |Cite
|
Sign up to set email alerts
|

Primary cerebral malignant melanoma

Abstract: Primary intracranial melanomas are uncommon and constitute approximately 1% of all melanoma cases and 0.07% of all brain tumors. In nature, these primary melanomas are very aggressive and can spread to other organs.We report an uncommon case of primary cerebral malignant melanoma—a challenging diagnosis guided by clinical presentations, radiological features, and surgical biopsy results, aiming to emphasize the importance of considering primary melanoma when making differential diagnoses of intracranial lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The prognosis also varies and there have been mixed outcomes reported in the literature as well as use of different treatment regimens. The mainstays of treatment for intraparenchymal melanotic tumors are complete resection and postoperative chemoradiotherapy, which result in a survival of up to 17 years in adults [ 2 ]. In contrast, the prognosis is poor in pediatric patients, with a median survival of 8 months after presentation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prognosis also varies and there have been mixed outcomes reported in the literature as well as use of different treatment regimens. The mainstays of treatment for intraparenchymal melanotic tumors are complete resection and postoperative chemoradiotherapy, which result in a survival of up to 17 years in adults [ 2 ]. In contrast, the prognosis is poor in pediatric patients, with a median survival of 8 months after presentation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the prognosis is poor in pediatric patients, with a median survival of 8 months after presentation [ 8 ]. The importance of recognizing this entity as part of our diagnostic repertoire is that the outcome also varies when compared to metastatic melanoma, which carries a survival rate of 5 to 6 months [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that trauma-induced coagulopathy is common in TBI patients [8][9][10] and the incidence of coagulation disorders has substantial heterogeneity, ranging from 7-54% [11,12]. Reasons for this variation include different techniques and de nitions used, the heterogeneity of the patients and the various testing times [13]. Secondary coagulopathy after TBI represent an important factor for unfavorable prognosis [14,15], resulting in a nine-fold higher risk of death and a 30-fold higher risk of poor prognosis than that in TBI patients without secondary coagulation disorders [7,9,16].…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma is a malignant tumor originating from melanocytes and often occurs in the skin, uvea, oral cavity, intracranial, etc. (Smith et al, 2016;Tang et al, 2017;Yang et al, 2018). According to the global cancer statistics in 2018, there are more than 280,000 new cases of melanoma of skin worldwide, accounting for 1.6% of new cancer cases; and more than 60,000 cases of melanoma deaths worldwide, accounting for 0.6% of total cancer deaths (Bray et al, 2018).…”
Section: Introductionmentioning
confidence: 99%